A multicenter phase 1 study of plerixafor and rituximab in patients with chronic lymphocytic leukemia. Issue 14 (6th December 2019) - Andritsos, Leslie A.; Byrd, John C.; Cheverton, Peter; Wu, Jingyang; Sivina, Mariela; Kipps, Thomas J.; Burger, Jan A.
Abstract: CXCR4 directs chronic lymphocytic leukemia (CLL) trafficking within protective tissue niches, and targeting CXCR4 with plerixafor may enhance drug sensitivity. We performed a phase 1 dose escalation study of plerixafor (NCT00694590) with rituximab in 24 patients with relapsed/refractory CLL. Patients received rituximab 375 mg/m 2 on days 1, 3, and 5, followed by bi-weekly rituximab plus dose-escalated plerixafor for 4 weeks. The maximum tolerated dose of plerixafor was 320 µg/kg. The most common toxicities were fatigue (13 patients, 57%), nausea (11, 48%), chills (10, 43%), and diarrhea and dyspnea (seven, 30% each). No patients developed symptomatic hyperleukocytosis or tumor lysis syndrome. A median 3.3-fold increase (range 1.2–12.4) in peripheral blood CLL was seen following the first dose of plerixafor, confirming CLL cell mobilization. The overall response rate was 38% and correlated with higher doses of plerixafor. Plerixafor is well-tolerated in patients with CLL; further tumor sensitization studies with CXCR4 antagonists are warranted.